My Amish boyfriend : a novel - Carlson, Melody (Revell, a division of Baker Publishing Group, 2014)
Sixteen-year-old Shannon McNamara has exciting plans for the summer, and she can't wait to get to them. Unbeknownst to her, however, her widowed and ailing mother has plans of her own--to relocate them both to the heart of Amish country in Ohio where she has relatives who can look after her. Shannon quickly learns that living a "simple" life is actually a lot of hard work. But when a hot young Amish guy named Ezra enters the picture, she's ready to get an Amish makeover and even consider making it a permanent change. But does Ezra share her attraction? Will Shannon really make the jump into this new way of life? And will it be for the right reasons?